2008
DOI: 10.1103/physrevlett.100.227601
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Phase Diagram of Ferroelectric(Ba,Ca)TiO3Single Crystals with Giant Electromechanical Response

Abstract: We report the anomalous phase evolution in ferroelectric single crystals Ba1-xCaxTiO3 (0.02 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
137
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 25 publications
14
137
1
Order By: Relevance
“…Fu firstly described this phase diagram in Ba 1−x Ca x TiO 3 single crystal, and suggested that the displacement of Ca stabilized the total energy of the unit cell. 10 The suppressed phase transitions due to Ca-substitution, especially for x ≥ 0.23, has also been interpreted by the soft-mode theory, which suggested that the off-centering nature of Ca could suppress the hopping of Ti ions and then reduce damping of the soft-mode. 18 Recently, Levin et al revealed the local structure origins of this phenomenon: both ferroelectric Ca displacements and their amplification of the Ti off-centering.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fu firstly described this phase diagram in Ba 1−x Ca x TiO 3 single crystal, and suggested that the displacement of Ca stabilized the total energy of the unit cell. 10 The suppressed phase transitions due to Ca-substitution, especially for x ≥ 0.23, has also been interpreted by the soft-mode theory, which suggested that the off-centering nature of Ca could suppress the hopping of Ti ions and then reduce damping of the soft-mode. 18 Recently, Levin et al revealed the local structure origins of this phenomenon: both ferroelectric Ca displacements and their amplification of the Ti off-centering.…”
Section: Resultsmentioning
confidence: 99%
“…The previous work of first principle calculation indicated that Ca 2+ ions shifted to the off-centering positions due to its smaller ionic radius (1.34Å) than that of Ba (1.61Å), 15 leading to a local polarization in the A-site of the perovskite structure. 10 Levin's refinement results suggested that Ca had its own additional displacement as well as influenced the Ti displacement. 11 Our results reinforce these suggestions and evaluate the polarization in details.…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] These outstanding dielectric properties are due to the proximity of the Curie temperature (T c ) to the room temperature at around 100 • C. However, the dielectric properties of BaTiO 3 -based materials degrade dramatically at higher temperatures above 200 • C, because these properties obey the Curie-Weiss law in the paraelectric phase. 8,9 In a previous work, we proposed thin films of bismuth-layered perovskite dielectrics, such as CaBi 4 Ti 4 O 15 with its c-axis orientation, as candidate materials for high-temperature capacitor applications.…”
Section: Introductionmentioning
confidence: 99%